Technology Prospecting on Enzymes for the Pulp and Paper Industry - Braz Jose Demuner; Nei Pereira Junior; Adelaide M.S. Antunes (Journal of Technology Management & Innovation, 2011)
The use of enzymes in the pulp and paper industry was introduced in the 1986. However, their use has been relatively minor. This prospective study aims at enhancing the understanding of the most important advances regarding the use of enzymes in this industry and to identify the future trends of this technology. Information gathered from the Web of Science shows a growing number of papers published on this topic indicating an increased interest in this issue. A study on patents also displayed a high number documents related to this technology. Cellulase, xylanase, laccase and lipase are the most important enzymes that can be used in the pulp and paper processes. Furthermore, the key objectives of enzymes development have been in the bleaching boosting with xylanases and fiber modification with cellulases. The current and future trends on the development of enzymes are focused on increasing their thermostability and their alkalinity strength.